2021
DOI: 10.1039/d0cp05668e
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory budding dynamics of a chemical garden within a co-flow of reactants

Abstract: The oscillatory growth of chemical gardens is studied experimentally in the budding regime using a co-flow of two reactant solutions within a microfluidic reactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In these studies, one reactant is injected into a larger reservoir containing the second reactant. Microfluidic devices further simplify this approach and allow for the production of nearly linear precipitate structures along the interface of laminarly co-flowing reactant streams. Such experiments revealed that many precipitate membranes have a constant width along the flow channel and thicken strictly in the direction of the metal salt solution. , The corresponding growth dynamics obey a square root law w ∝ ( D eff t ) 1/2 where w is the membrane width, t is time, and D eff is an effective diffusion coefficient that depends linearly on OH – concentration. , For Ni­(OH) 2 membranes, D eff values equal about 10 –7 cm 2 /s, which is 100 times smaller than the diffusion coefficient of small ions in water …”
Section: Introductionmentioning
confidence: 99%
“…In these studies, one reactant is injected into a larger reservoir containing the second reactant. Microfluidic devices further simplify this approach and allow for the production of nearly linear precipitate structures along the interface of laminarly co-flowing reactant streams. Such experiments revealed that many precipitate membranes have a constant width along the flow channel and thicken strictly in the direction of the metal salt solution. , The corresponding growth dynamics obey a square root law w ∝ ( D eff t ) 1/2 where w is the membrane width, t is time, and D eff is an effective diffusion coefficient that depends linearly on OH – concentration. , For Ni­(OH) 2 membranes, D eff values equal about 10 –7 cm 2 /s, which is 100 times smaller than the diffusion coefficient of small ions in water …”
Section: Introductionmentioning
confidence: 99%
“…i k j j j j j j j j y { z z z z z z z z (14) This gives the radius of the precipitate structure as a function of time, considering the contributions of injection, osmosis, reaction, and density change. If reaction and osmosis are neglected, then ρ eff ≈ ρ Co , reducing eq 13 to…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…Pattern formation is commonly observed in nature as a result of physical, chemical, or biological self-organizing processes. , A remarkable example of such self-organizing patterns are chemical gardens, precipitate structures formed when a metal salt contacts with a solution of silicate, phosphate, carbonate, or many other anions. Various methods have been developed to grow these structures, which lead to a wide array of patterns and regimes; the one characteristic common to all is the formation of a semipermeable precipitate membrane separating two fluids which establishes a steep concentration and pH gradient. The earliest such experimental method is seed growth, which simply involves placing a solid crystal of a metal salt in a reservoir containing a silicate solution.…”
Section: Introductionmentioning
confidence: 99%
“…6 This chemical garden phenomenon has been discovered to occur in nature as hydrothermal vents or chimneys [7][8][9][10] and rusts on metals. 11,12 Scientists are now focusing on the formation mechanism, 13 the growth behavior, 14 periodic membrane rupture, 15 surface instabilities 16 or even pattern formation 17,18 and the dynamics in thin solution layer. 19,20 The fascination with chemical gardens has not stopped within the Earth's ground gravity.…”
Section: Introductionmentioning
confidence: 99%